Laccase immobilization and surface modification of activated carbon fibers by bio-inspired poly-dopamine. Issue 26 (17th April 2018) - Zhang, Chencheng; Gong, Lili; Mao, Qinghui; Han, Pingfang; Lu, Xiaoping; Qu, Jiangang
Abstract : In this study, we developed a new synthesis method for modifying activated carbon fibers (ACFs) by dopamine with oxidation-based self-polymerization (DA-ACFs). Abstract : In this study, we developed a new synthesis method for modifying activated carbon fibers (ACFs) by dopamine with oxidation-based self-polymerization (DA-ACFs). In addition, laccase was immobilized on the surface of unmodified ACFs (L-ACFs) and DA-ACFs (LDA-ACFs) via cross-linking after being incubated for 12 h at 5 °C. The surface composition and microstructure of the samples were characterized by scanning electron microscopy, X-ray photoelectron spectroscopy, attenuated total reflectance Fourier-transform infrared reflection and thermo-gravimetric analysis. The optimized laccase concentration for preparing the samples was 2.0 g L −1 . The results demonstrated that the successful poly-dopamine modification increased the catalytic abilities of the ACFs in terms of biocompatibility and hydrophilicity. Compared with free laccase, the immobilized laccase exhibited significantly higher relative activity over a pH range of 3.5–6.5 and a temperature range of 30–60 °C; the thermo-stability increased, and 50% relative activity of the LDA-ACFs remained after 5 h at 55 °C. After six cycles of reuse, the relative activity of LDA-ACFs remained ≥60%, compared to 40% activity remaining for L-ACFs, and long-term storage stability was demonstrated. Moreover, the kinetic parameters ( K m ) of the two immobilized laccases were both higher than that of free laccase, whereas the maximum velocities ( V max ) were lower. These results indicate that the DA-ACFs are economical, simple, and efficient carries for enzyme immobilization, and can be suitable for further biotechnology and environmental applications.